LOAD AND RESISTANCE FACTOR CALIBRATION METHODOLOGY FOR OFFSHORE JACKET PLATFORMS IN MALAYSIA - Sambu Potty, Narayanan (Proceedings, 2010)
This paper deals with the methodology for determining the Load and Resistance Factors for the structural design of jacket platforms. The environmental load factors used currently for design in Malaysia are made either in the context of Hurricanes of Gulf of Mexico or winter storms of North Sea. These environmental conditions are much more severe compared to those in the Monsoon season in South China Sea. This means that the design of fixed offshore platforms can be economized. Using SACS software, existing platforms will be analyzed and designed as per API RP2A WSD and then will be redesigned as per API RP2A LRFD. Using appropriate distributions for the variables, FORM and Monte Carlo simulations will be applied to find out reliability index (β) of the typical members of the platform designed using API RP 2A WSD. Target reliability indices for different category of members are determined and then the load and resistance factors.Various methods followed for the calibration of the codes will be reviewed. The application of this for the future development of PTS (2005) code in Malaysia is also discussed.